Skin mastocytoma in dogs, complex treatment and survival of animals - B. B. Ivashkiv; A. R. Mysak (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The article deals with highlighting the results of clinical investigations of 49 dogs with cutaneous mastocytomas (MCTs), which during 2016–2024. took a full course of diagnostic and therapeutic measures in the clinic of the Department of Surgery of Stepan Gzhytsky LNUVMB. 26 male dogs and 23 female dogs were involved in the research, they were of different breeds, uncastrated, aged from 4 to 16 years (median 9.5 and mode 9–10 years). The purpose of the current stage of research was clinical and experimental substantiation of the complex treatment of dogs for skin mastocytomas, setting its therapeutic effectiveness and animal survival. It was established that in the structure of skin tumor lesions in dogs, MCTs reach 17.2 %. During the initial examination of animals, in accordance with the criteria of the clinical TNM classification of neoplasias, at the time of admission to the clinic, the following were diagnosed: in 20.5 % of dogs – I, in 26.53 % – II, in 51.02 % – III and in 2.04 % in some cases – the IV clinical stage of the development of the tumor process. The diagnosis of mastocytoma was set up on the basis of the data of the physical examination of animals and cytological verification of the biopsy material got during targeted, ultrasound-guided, fine-needle biopsy of neoplasias and regional lymph nodes. The final diagnosis was got based on the results of a histological investigation of the excisional material taken during the operation. According to the criteria of the two-stage histological classification (Kiupel), skin mastocytomas were verified as low-malignant in 33 (67.3 %) dogs and highly malignant in 16 (32.7 %). For experimental research, sick dogs were divided into four groups: the first (n = 16) and second (n = 17) included animals with low malignancy, and, accordingly, the third (n = 8) and fourth (n = 8) with high malignant MCTs. In the scheme of treatment of all animals, a surgical method was used, while in the first group, surgical removal of tumors was the main treatment measure, in the second, third and fourth groups, surgery was only the first stage of treatment. In order to prevent the degranulation of mast cells and, accordingly, to prevent the occurrence of inflammation and swelling in the tumor and in the surrounding tissues after surgery, as well as to reduce the volume of tumors before surgery, neoadjuvant glucocorticoid therapy was performed. After the surgical removal of tumors, the animals of the first group were only observed for their recovery and further life. At the same time, in the dogs of the second group, after extirpation of neoplasms, the immunostimulating preparation anfluron was used for 24 days. The dogs of the third group were given two courses of chemotherapy according to the vinblastine, cyclophosphamide, and dexamethasone scheme after the operation. In the dogs of the fourth group, similarly to the third group, tumors were surgically removed, chemotherapy was performed according to the same scheme, however, after completion of the latter, the animals were used anfluron, according to the scheme as in the second group. According to the results of the use of dexamethasone by means of neoadjuvant therapy in 77.5% of dogs, a decrease in the size of tumors by 19.2–25.8 % was set up, which made it possible to extirpate tumors within a wide range of the surgical field (with a margin margin >2 cm), in 18.4% of animals the size of the tumors did not change and in 4.1% a slight increase in neoplasia was noted. The therapeutic effectiveness of the performed measures was got based on the results of the clinical condition investigation, as well as indicators of overall survival, recurrence-free survival of animals, and median life expectancy. The survival rate was also evaluated by constructing graphs and analyzing Kaplan-Meier curves. According to the results of clinical researches and two-year observations, the survival rate of dogs in the first and second groups was 100 % during the first year, 50.0% in the third, 62.5 % in the fourth, and 62.5 % in the first, 62.5 % in the second, and 62.5 % in the fourth. 70.6 %, the third 12.5 % and the fourth – 25 %. It was set up that the median life expectancy among dogs with highly malignant mastocytomas was 7 months in the third group and was significantly shorter compared to the animals of the fourth group of 19 months (P < 0.05), which were treated with anfluron (recombinant α-γ-interferons). At the same time, among dogs with mastocytomas of low malignancy, after surgical removal of neoplasias and the use of immunotherapy, a smaller number of cases of local recurrence and metastasis to lymph nodes were got. Therefore, it can be concluded that a multimodal approach to the treatment of dogs with MCTs, which includes a combination of surgery, chemotherapy and immunotherapy adapted to the profile of each patient, can improve the survival rates and quality of life of the animals.